Measurement of Angular Parameters From the Decay B0›k*0µ+µ-In Proton–proton Collisions at S=8tev - CMS Collaboration; Karapınar, Güler; Karapınar, Güler (Elsevier Ltd., 2018)
Angular distributions of the decay B0→K⁎0μ+μ− are studied using a sample of proton–proton collisions at s=8TeV collected with the CMS detector at the LHC, corresponding to an integrated luminosity of 20.5fb−1. An angular analysis is performed to determine the P1 and P5 ′ parameters, where the P5 ′ parameter is of particular interest because of recent measurements that indicate a potential discrepancy with the standard model predictions. Based on a sample of 1397 signal events, the P1 and P5 ′ parameters are determined as a function of the dimuon invariant mass squared. The measurements are in agreement with predictions based on the standard model.
Keywords: Flavor physics; Angular analysis; Particle decays; Particle detectors